Microstrip Bandstop Filter for Preventing Conduction Electromagnetic Information Leakage of High-Power Transmission Line - Xueyun Han; Xiaosong Li; Yingping Zhou; Pengfei Zheng; Haohua Cui; Xiaonan Zhang (International Journal of Antennas and Propagation)
The research of transient electromagnetic pulse emission monitoring technology (TEMPEST) protection is essential. Based on microstrip bandstop filter (MSBSF), a method to prevent electromagnetic information leakage of high-power transmission lines is proposed in this paper. The MSBSF with a high insertion loss and carrying large current in the frequency of 2.40–2.49 GHz is designed, fabricated, and experimentally measured. The fabricated MSBSF with the insertion loss of 38 dB at 2.41–2.49 GHz can carry a current greater than 10A and withstand a voltage of 1.7 kV. Compared with the traditional electromagnetic interference (EMI) filter, the MSBSF has the advantages of preventing conducted electromagnetic information leakage in the high-frequency bands, carrying greater current subject to higher voltage, and possessing lighter weight. The MSBSF may be used to prevent the leakage of high-frequency electromagnetic information of high-power transmission lines.